2022
DOI: 10.1038/s41419-022-05434-z
|View full text |Cite
|
Sign up to set email alerts
|

Activation of orphan receptor GPR132 induces cell differentiation in acute myeloid leukemia

Abstract: Blocked cellular differentiation is a critical pathologic hallmark of acute myeloid leukemia (AML). Here, we showed that genetic activation of the orphan GPCR GPR132 significantly induced cell differentiation of AML both in vitro and in vivo, indicating that GPR132 is a potential trigger of myeloid differentiation. To explore the therapeutic potential of GPR132 signaling, we screened and validated a natural product 8-gingerol (8GL) as a GPR132 agonist. Notably, GPR132 activation by 8GL promoted differentiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…CD207 is a glycosylated receptor that acts as a specific receptor of Langerhans cells, processing of antigen for presentation to T cells 48 . GPR132 is a leukemia orphan receptor that has the potential to trigger myeloid differentiation 49 . In acute myeloid leukemia patients, high expression of SLC7A11 is associated with poor prognosis 50 , 51 .…”
Section: Discussionmentioning
confidence: 99%
“…CD207 is a glycosylated receptor that acts as a specific receptor of Langerhans cells, processing of antigen for presentation to T cells 48 . GPR132 is a leukemia orphan receptor that has the potential to trigger myeloid differentiation 49 . In acute myeloid leukemia patients, high expression of SLC7A11 is associated with poor prognosis 50 , 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have shown that the inhibition of the mTOR signaling pathway can promote tumor cell differentiation 23 . mTOR inhibitors, such as rapamycin and its derivatives, have been used to promote the differentiation of certain tumor cells and have shown therapeutic effects, possibly by affecting transcription factors, cell cycle regulation, and cell signaling in tumor cells 24 .…”
Section: Discussionmentioning
confidence: 99%
“…HEK293 cells were cotransfected with 0.5 μg of EP4-Tango, 1.0 μg of β-arrestin-TEV, and 1.0 μg of tTA-Luc plasmid using PEI as the transfection reagent in a 6.0 cm dish . Transfected cells were seeded into 96-well plates (3.0 × 10 4 cells/well) and incubated at 37 °C overnight.…”
Section: Methodsmentioning
confidence: 99%